Technological design as practice: a look beyond artifactual instrumentalism and merely human agency - Carvalho, Helder Buenos Aires de (Argumentos - Revista de Filosofia, 2024)
The paper is based on the thesis that technological creation or design should not be viewed as an activity entirely determined by internal criteria for developing artifacts, as if these could have only a single, identical form and function, depending solely on their material properties. Like any other socially established human practice, technological creation or design is a human action and, as such, is subject to moral and political evaluations. For this purpose, we adopt Alasdair MacIntyre’s neo-Aristotelian perspective and his concept of practice, in which the normative dimension of practices is not an external factor applied to them but is constitutively internal, stemming from a telos that defines them as parts or forms of realizing human excellence. In this sense, technological design is not axiomatically neutral but ontologically related to the social and political determinations linked to human actions and their various possibilities of material and symbolic being. Thus, it is a social practice that carries both internal and external ends and values in the MacIntyrean sense, and it cannot be understood outside the social fabric of which it is a part. Therefore, it bears ethical and political constitutive elements which, if disregarded in its constitution, obscure the complex nature of technology and its moral and political implications, dehumanizing it in its entirety.